IMPLEMENTATION OF GROSS MOTOR PHYSICAL ABILITIES IN CHILDREN AGED 5-6 YEARS THROUGH DRUM BAND MUSIC GAMES IN ISLAM NUSANTARA KINDERGARTEN - Cicih Sumiarsih; Hidayat, Amat; Ibnu Sina (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
This research was motivated by the significant gap between expectations and reality regarding the gross motor development of early childhood in Indonesia. This study aims to analyze the effectiveness of playing drum band music in improving the gross motor skills of children aged 5-6 years at the Islam Nusantara Kindergarten, with a focus on aspects of coordination, balance, strength and agility. This research uses a descriptive qualitative approach. The research subjects consisted of 10 children aged 5-6 years, 3 teachers at the Islam Nusantara Kindergarten and 2 parents of students. Data collection techniques include participant observation, semi-structured interviews with teachers, parents and children, and documentation. The research was carried out for 12 weeks with two drum band practice sessions per week. The results showed significant improvements in the children's gross motor skills. There was an increase in gross motor test scores after three months. The aspects most affected are coordination, balance, strength, and agility. Interviews with teachers and parents confirmed positive changes in children's daily physical activity. Drum band music games have been proven to be effective in improving the gross motor skills of children aged 5-6 years. This program provides an engaging and complex context for the simultaneous development of multiple aspects of gross motor skills